(untitled) (KULT_online, 2013)
More than 20 years after the breakdown of ’real-existing socialism’ in the eastern part of Europe, when the Marxist project, by its own measures as well as those of others, seemed to have failed and been discredited for all time, Karl Marx and his ideas gain appeal again. It may be due to the present worldwide economic crisis – probably the most serious collapse of capitalistic development since World War II – that during the last years a huge number of books, introductions, and criticisms appeared on the book market (see References). This fact lets us conjecture about a Renaissance of Marxism. Three of these recent publications are discussed here: The last book of the recently deceased British historian Eric Hobsbawm How to Change the World: Reflections on Marx and Marxism is an extensive study of the historical influence of Marxist theories; the defence of Marx, Where Marx is right, by the Catholic linguist Terry Eagleton tries to refute the top ten most popular aspects in criticism of Marxism; and Why Marx Was Right by the German sociologist Fritz Reheis wants to rehabilitate Marxist criticism of capitalism concerning the reproductive sphere with the aid of cross-reference with other theories. Choosing different assessments of and approaches to the subject, each of the books claims to throw light on aspects of Marxist philosophy and ideology or their historical influence in a clear way and to refute popular objections, but without being dogmatic. Although none of the selection is a full manual for Marxism, nevertheless each one has for itself the potential to satisfy the increased interest.